2015
DOI: 10.1016/j.jprot.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed serum proteins in gastric adenocarcinoma

Abstract: Gastric adenocarcinoma is an aggressive cancer with poor prognosis. Blood based biomarkers of gastric cancer have the potential to improve diagnosis and monitoring of these tumors. Proteins that show altered levels in the circulation of gastric cancer patients could prove useful as putative biomarkers. We used an iTRAQ-based quantitative proteomic approach to identify proteins that show altered levels in the sera of patients with gastric cancer. Our study resulted in identification of 643 proteins, of which 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 64 publications
(66 reference statements)
1
33
0
Order By: Relevance
“…This finding supports a recently published study which reported a 2.3‐fold increase in plasma SHBG level in GC patients compared to a control group as measured by iTRAQ‐based quantitative MS. However, that study did not validate plasma SHBG level in different study cohorts .…”
Section: Discussionmentioning
confidence: 88%
“…This finding supports a recently published study which reported a 2.3‐fold increase in plasma SHBG level in GC patients compared to a control group as measured by iTRAQ‐based quantitative MS. However, that study did not validate plasma SHBG level in different study cohorts .…”
Section: Discussionmentioning
confidence: 88%
“…For example, transgenic mice that overexpressed IGFBP-2 showed significantly higher blood glucose levels than controls at 30, 60 and 90 minutes during an oral glucose tolerance test, as well as lower levels of GLUT4–the insulin-dependent glucose transporter–at cell surfaces compared to controls [5]. Abnormally high IGFBP-2 levels are often an indicator of severe catabolic events, such as gastric cancer, anorexia nervosa and renal failure [6-8]. In a study of 625 men and women aged 70 and older, plasma IGFBP-2 significantly predicted mortality from all causes after adjusting for markers of body composition, as well as fasting glucose and insulin [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Polysulfoethyl columns from Poly‐LC (Neste group) have been by far the most widely used column type. Notable examples where SCX fractionation has been used include the study by Juhasz et al where it was used in combination with tandem depletion and LC‐MALDI, reporting 470 proteins detected in nine iTRAQ experiments, the ESI study of gastric adenocarcinoma by Subbannayya et al where they reported identification 643 proteins, and the ESI & MALDI study of Zhang et al where they reported 1044 proteins . SCX fractionation has mostly been performed off‐line, necessitating additional concentration and desalting steps.…”
Section: Methodsologymentioning
confidence: 99%